2014
DOI: 10.1089/gtmb.2014.0003
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Screening of the Neurexin 1 Gene in Thai Patients with Intellectual Disability and Autism Spectrum Disorder

Abstract: Mutation screening of the NRXN1gene in patients with ID and ASD may be useful to identify potential variants predisposing to ID and ASD. However, further studies utilizing protein functional analysis of the novel variants are required for a more definite conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The top 10 most strongly autism-correlating empirically-identified transcripts/proteins are depicted in a heatmap format in Figures 6D,E (elevated compared to control = red; decreased compared to control = green). From the transcript analysis, we identified the involvement of neurexin 1 (Yangngam et al, 2014 ) and Wolframin syndrome 1 (Wfs1; Chakrabarti et al, 2009 ). From the protein analysis, we again identified Wfs1 as a strong autism-related link, Fam120c (De Wolf et al, 2014 ), and Bassoon (Bsn; Yoshida et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The top 10 most strongly autism-correlating empirically-identified transcripts/proteins are depicted in a heatmap format in Figures 6D,E (elevated compared to control = red; decreased compared to control = green). From the transcript analysis, we identified the involvement of neurexin 1 (Yangngam et al, 2014 ) and Wolframin syndrome 1 (Wfs1; Chakrabarti et al, 2009 ). From the protein analysis, we again identified Wfs1 as a strong autism-related link, Fam120c (De Wolf et al, 2014 ), and Bassoon (Bsn; Yoshida et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Loss-of-function variants in NRXN1 have been identified in patients with ASD in multiple cohort studies (Marshall et al, 2008; Morrow et al, 2008; Glessner et al, 2009). A wide spectrum of developmental disorders including ID without ASD (Camacho-Garcia et al, 2012; Yangngam et al, 2014), language delay, mild dysmorphic features, and hypotonia (Ching et al, 2010), as well as neuropsychiatric conditions like SCZ have also been reported in patients with NRXN1 variants. In contrast, variants in NRXN2 and NRXN3 are much rarer, but accumulating reports provide evidence supporting an association between these two genes and ASD, as well as other neurodevelopmental and neuropsychiatric conditions (Gauthier et al, 2011; Vaags et al, 2012; Yuan et al, 2018).…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
“…Neurexins ( NRXN ) are synaptic adhesion proteins that localize to the membrane of the presynapse and bind Neuroligins (NLGNs), which are localized on the postsynaptic membrane. There are three genes within the NRXN family ( NRXN1 , NRXN2 , and NRXN3 ) with multiple mutations or copy number variations having been identified in NRXN family members in ASD diagnoses (Feng et al, 2006 ; Autism Genome Project Consortium et al, 2007 ; Bremer et al, 2011 ; Yangngam et al, 2014 ). NRXN1 mutations have also been identified in multiple neuropsychiatric disorders, including Tourette syndrome, schizophrenia, ADHD and bipolar disorder (Stone et al, 2008 ; Guilmatre et al, 2009 ; Zhang et al, 2009 ; Sundaram et al, 2010 ; Lionel et al, 2011 ).…”
Section: Alterations In Synaptic Components In Asdmentioning
confidence: 99%